Evaluasi Penerapan Pengawasan Mutu Jagung Sebagai Bahan Pakan di Indonesia: Evaluation of Corn Quality Control Implementation as Feedstuffs in Indonesia - Usman Ali; Yuli Retnani; Anuraga Jayanegara (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2023)
Corn is the main component in the manufacture of feed which functions as an energy source for poultry and ruminants. Requirements for the quality of corn as a feed ingredient are regulated in the Indonesian National Standard (SNI) for corn which includes moisture content, damaged seeds, mouldy seeds, foreign matter and aflatoxin. The purpose of this reserch was to evaluated and analyzed the quality of corn whether it was in accordance with SNI 2020. In this research, secondary data was used that obtained from six of feed testing laboratories and three feed mills, spread across Indonesia, including: West Java, Central Java, East Java, Banten, South Sulawesi and North Sumatera. The total sample from the feed testing laboratories were 403 samples and feed mills were 5.161 samples. One sample T-test was used to analyze the result from feed testing laboratories and feed mills compare to the 2020 SNI quality values. The result of one sample T-test showed that the result of moisture content, damage seeds, moldy seeds, and foreign matter were still not in accordance with SNI. Meanwhile, aflatoxin was already fulfilled SNI.